Frazeologiczny związek wyrazowy "polski hydraulik" <polnischer Klempner> w polskim i niemieckim dyskursie publicznym w 2005 roku = Phraseological collocation "polski hydraulik" <polnischer Klempner> <Polish Plumber> in the German and Polish Discourse 2005 - Dąbrowska-Burkhardt, Jarochna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study in politolinguistics and discourse analysis discusses the work-related migration within the European Union in 2005. The interest of this study is not only in the content of political debate, strongly emphasized in the Polish and German press, but specifically in distinctive figures of speech. At the center of interest is the phraseological collocation "polskiHydraulik" [Polish] and its German equivalent "polnischer Klempner", i.e.
Keywords: analiza dyskursu; politolingwistyka; analiza prasy polskiej i niemieckiej z 2005 r.; "polski hydraulik"; migracja zarobkowa; Unia Europejska; discourse analysis; politolinguistics; "Polish plumber"; analysis of German and Polish newspaper articles from 2005; work-related migration